2017
DOI: 10.1103/physrevlett.118.080402
|View full text |Cite
|
Sign up to set email alerts
|

Polynomial Monogamy Relations for Entanglement Negativity

Abstract: The notion of non-classical correlations is a powerful contrivance for explaining phenomena exhibited in quantum systems. It is well known, however, that quantum systems are not free to explore arbitrary correlations-the church of the smaller Hilbert space only accepts monogamous congregants. We demonstrate how to characterize the limits of what is quantum mechanically possible with a computable measure, entanglement negativity. We show that negativity only saturates the standard linear monogamy inequality in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…One of the most important issues closely related to entanglement measure is the monogamy relation of entanglement [23], which states that, unlike classical correlations, if two parties A and B are maximally entangled, then neither of them can share entanglement with a third party C. An important question in this field is to determine whether a given entanglement measure is monogamous. Considerable efforts have been devoted to this task in the last two decades [19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] ever since Coffman, Kundu, and Wootters (CKW) presented the first quantitative monogamy relation in Ref. [19] for threequbit states.…”
mentioning
confidence: 99%
“…One of the most important issues closely related to entanglement measure is the monogamy relation of entanglement [23], which states that, unlike classical correlations, if two parties A and B are maximally entangled, then neither of them can share entanglement with a third party C. An important question in this field is to determine whether a given entanglement measure is monogamous. Considerable efforts have been devoted to this task in the last two decades [19,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] ever since Coffman, Kundu, and Wootters (CKW) presented the first quantitative monogamy relation in Ref. [19] for threequbit states.…”
mentioning
confidence: 99%
“…In contrast with the classical world, it is not possible to prepare three qubits A, B, C in a way that any two qubits are maximally entangled [1]. In fact, if qubit A is maximally entangled with qubit B, then it must be uncorrelated (not even classically) with qubit C. This phenomenon of monogamy of entanglement was first quantified in a seminal paper by Coffman, Kundu, and Wootters (CKW) [1] for three qubits, and later on studied intensively in more general settings [2,3,4,5,14,15,6,16,17,18,7,19,20,21,22,23,24,25,8,9,26,27,10,11,28,29,30,12,13,31,32,33,34,35,36,37,38,39,40].…”
mentioning
confidence: 99%
“…This was already apparent in the seminal work of [1] in which E was taken to be the square of the concurrence and not the concurrence itself. More recently, it was shown that many other measures of entanglement satisfy the monogamy relation (1) if E is replaced by E α for some α > 1 [13,8,12,5,7,11,9,6,10].…”
mentioning
confidence: 99%
“…In order to prove the functional indepedence for the right-hand sides of the constraints in Eq. (17) in the main text, we need to show that if for all ρ,…”
Section: Appendix C: Functional Independence Of the Correlation Constmentioning
confidence: 99%
“…Compatibility of marginals.-Finally we want to highlight the relation of our results with the quantum-marginal problem, that is, the question whether or not a given set of reduced states is compatible with a joint global state [53]. Clearly, our linear-entropy constraints (17) represent necessary conditions for the reduced states ρ S to be compatible with the global state ρ. However, we can make new statements even at the operator level.…”
mentioning
confidence: 97%